Differences in sexually transmitted infection risk comparing preexposure prophylaxis users and propensity score matched historical controls in a clinic setting. (1st September 2019) - Montaño, Michalina A.; Dombrowski, Julia C.; Dasgupta, Sayan; Golden, Matthew R.; Manhart, Lisa E.; Barbee, Lindley A.; Duerr, Ann; Khosropour, Christine M.
Abstract : Objective: The aim of this study was to determine whether MSM using preexposure prophylaxis (PrEP) are at a higher risk of bacterial sexually transmitted infections (STIs) than MSM not using PrEP. Design: Secondary analysis of longitudinal STI data obtained from MSM attending an STD Clinic in Seattle, Washington, USA, October 2011–September 2017. Methods: We identified patients obtaining PrEP through the STD Clinic, and used propensity score matching to select a historical group of similar patients not using PrEP for comparison. We linked patient data with STI surveillance data to compare the incidence of chlamydia, gonorrhoea and early syphilis, and time to first symptomatic STI among PrEP users and nonusers. Results: Three hundred and sixty-five PrEP users who picked up prescriptions and returned for follow-up and 730 propensity score matched nonusers were included in the analysis. Adjusted incidence rate ratios (aIRRs) for chlamydia, gonorrhoea and early syphilis were 3.2 [95% confidence interval (95% CI): 1.9–5.3], 2.8 (95% CI: 1.7–4.6) and 2.9 (95% CI: 1.5 – 5.6), respectively, comparing PrEP users to nonusers. Time to first symptomatic STI was shorter among PrEP users (120 days, 95% CI: 77 – 171) than among nonusers (185 days, 95% CI: 163–256). Conclusion: Among MSM on PrEP, we observed a higher incidence of STIs and faster time to first symptomatic STI than MSM not using PrEP. PrEP may be a contributing factor in increasing STI rates among MSM. Abstract : Supplemental Digital Content is available in the text